Nut consumption in Portugal: the balance between the risks and the benefits regarding liver cancer and cardiovascular disease - Assunção, Ricardo (2020)
Nuts are rich sources of cis-unsaturated fatty acids, fibre, vitamins, minerals, and a number of bioactive substances and the regular consumption of nuts are being associated with a reduction in all-cause mortality, particularly cardiovascular disease (CVD). At the same time, the occurrence of mycotoxins in nuts, including the most potent carcinogenic aflatoxins (AFTs), has been reported by several authors worldwide. According to the National Food, Nutrition and Physical Activity Survey (IAN-AF 2015-16), the usual consumption of nuts by the Portuguese adults is 2.7 g/day. Some recent epidemiological studies (e.g. PREDIMED) suggested that a daily nuts consumption of 30 g could reduce the incidence of CVD. The present study aimed to quantify the health impact in terms of Disability-adjusted life years (DALY) of increasing nut consumption to 30 g/day by adult Portuguese population, when compared to the current intake. Regarding nut consumption, two scenarios were established: current consumption (CS) – 2.7 g/day; alternative scenario (AS) – 30 g/day. AFTs occurrence in nuts available in Portuguese market and nut consumption data were used to estimate AFTs intake. Epidemiological and National population data were used to estimate the DALYs, considering two different endpoints: the occurrence of hepatocellular carcinoma due to exposure to AFTs (IPSC/WHO) and the prevention of acute myocardial infarction due to nuts’ consumption (PREDIMED). A mean daily intake of AFTs of 0.013 (CS) and 0.142 (AS) ng/kg bw/day was predicted. This intake is estimated to cause 0.013 (CS) and 0.15 (AS) extra cases of Hepatocellular Carcinoma, corresponding to 0.2 (CS) and 2.7 (AS) annual DALYs. In contrast, the estimated number of preventable cases of myocardial infarction due to the increasing of nut consumption to 30 g/day was 1402 and the DALYs gained was 5658. Integrating risks and benefits, 5656 annual DALYs could be potentially saved. These results suggest an overall beneficial health effect of increased nut consumption in Portugal. Therefore, it seems not advisable to reduce exposure to AFTs by recommending a reduced intake of nuts.